A revision of the South American species of the cleptoparasitic bee genus Triepeolus Robertson, 1901 (Hymenoptera: Apidae) - Onuferko, Thomas M.; Rightmyer, Molly G.; Melo, Gabriel A.R.; Roig-Alsina, Arturo (European Journal of Taxonomy, 2024)
The cleptoparasitic bee genus Triepeolus Robertson, 1901 (Hymenoptera: Apidae) is revised for species occurring in South America. A total of nine species are confirmed from the continent, of which T. tuberculifer Onuferko, Rightmyer & Roig-Alsina sp. nov. is newly described. Four new synonymies are proposed: T. aguilari Moure, 1955 syn. nov. and T. megadelphus Cockerell, 1914 syn. nov. under T. buchwaldi (Friese, 1908); T. bilineatus Cockerell, 1949 syn. nov. under T. flavipennis (Friese, 1916); and Epeolus merus Brèthes, 1909 syn. nov. under T. nemoralis (Holmberg, 1886). Males of T. alvarengai Moure, 1955 and T. rufotegularis (Ashmead, 1900) and females of T. atoconganus Moure, 1955 and T. cecilyae Packer, 2016 are described for the first time. Lectotypes are designated for the following (all originally described under Epeolus Latreille, 1802 but now recognized as Triepeolus): E. buchwaldi, E. flavipennis, E. osiriformis Schrottky, 1910 and its junior synonym E. luteipes Friese, 1916, and E. rufotegularis. Diagnoses and complete descriptions/redescriptions are provided for all species, along with a fully illustrated dichotomous identification key (with Portuguese and Spanish versions available as supplementary material) to distinguish them based on external morphological features. Additionally, known collection records and information about the ecology of the treated species are presented.